PENGABDIAN MASYARAKAT PENYULUHAN PERAKITAN LAMPU PENERANGAN BERTENAGA SURYA KEPADA MASYARAKAT NAMBANGAN - Syamsuri; Miftahul Ulum; Bambang Setyono; Gatot Setyono; Suheni; Dwi Khusna; Ali Khomsah; Ardi Noerpamoengkas; Desmas Arifianto Patriawan; Vuri Ayu Setyowati; Hery Irawan; Hasan Syafik Maulana; Zain Lillahulhaq; Iftika Philo Wardani; Frizka Vietanti; Ahmad Anas Arifin; Afira Ainur Rosidah (Journal of Science and Social Development, 2020)
Kampung Nambangan Perak is located in Kelurahan Kedung Cowek, Bulak District, Surabaya, East Java. The majority of Nambangan residents work as fishermen. The Nambangan community is still unfamiliar with the use of alternative energy such as solar cells to replace fuel oil. The road access of village environment was only illuminated independently by installed map of people’s residents. The dim road conditions can cause a sense of alertness to residents and road users who spent the night. In addition, the installation of lamps with greater power can burden the economy of residents due to rising electricity prices. Based on field observations and direct interviews with local residents, there were three focuses aspects of this community service program, namely the introduction of alternative energy to residents, installation and guidance of lamp maintenance equipped with solar panels. Along with the implementation of guidance and education program for the Nambangan community, it is hoped that the residents will understand and feel familiar with the availability of alternative energy. The residents are also expected to be able to apply the use of alternative energy in their daily life. In addition, residents are expected to be able to carry out the process of assembling and maintaining alternative energy sources, especially solar panels.